Fibroblast growth factor 3 promotes spontaneous mammary tumorigenesis in Tientsin albino 2 mice via the FGF3/FGFR1/STAT3 pathway - Chen, Lankai; Zhang, Xipeng; Liu, Guisheng; Chen, Shuo; Zheng, Minying; Zhu, Siwei; Zhang, Shiwu (Frontiers in Oncology, 2023)
Introduction Tientsin albino 2 (TA2) mice can develop spontaneous breast cancer (SBC), which is associated with multiple pregnancies and infection with the mouse mammary tumor virus (MMTV). In this study, we sought to elucidate the molecular mechanisms underlying the development of SBC in TA2 mice induced by MMTV. Methods The integration site of MMTV in TA2 SBC was identified using whole-genome sequencing. The expression of fibroblast growth factor 3 (FGF3) in SBCs and normal breast tissues was compared. The primary cell line, TA-1106, derived from SBC, was cultured. The proliferation, cell cycle, migration, invasion, and tumorigenicity abilities, as well as the expression of epithelial-mesenchymal transition-related proteins, phosphorylated STAT3, and phosphorylated Akt, were assessed in MA-891cell line from TA2 and TA-1106 cells after FGF3 knockdown. The binding of FGF3 to FGF receptor 1 (FGFR1) was determined by co-immunoprecipitation. Additionally, the relationship between STAT3 and Akt phosphorylation was investigated using a small molecule inhibitor and STAT3 knockdown. Results MMTV integrated upstream of the FGF3 gene, and the FGF3 protein was highly expressed in TA2 SBCs. FGF3 knockdown in MA-891 and TA-1106 decreased their proliferation, migration, and invasion abilities, affected the cell cycle and expression of epithelial-mesenchymal transition-related proteins, and inhibited the growth of animal xenografts. FGF3 binds to FGFR1, and either FGF3 or FGFR1 knockdown decreases STAT3 and Akt phosphorylation levels. Inhibition of phosphorylation or expression of STAT3 resulted in decreased Akt phosphorylation levels. Inhibition of Akt phosphorylation also resulted in decreased STAT3 phosphorylation levels. Furthermore, treatment of MA-891 and TA-1106 cells with Wortmannin or Stattic caused FGFR1 upregulation in addition to inhibiting Akt or STAT3 phosphorylation. Conclusion The results of this study demonstrate that FGF3 plays a significant role in the development of SBC through the FGF3/FGFR1/STAT3 signaling pathway. There is a reciprocal activation between STAT3 and Akt. Inhibition of STAT3 or Akt phosphorylation promoted the expression of FGFR1. Validating the conclusions obtained in this study in human breast cancer (HBC) may contribute to targeted therapy and it is worth exploring whether the homologous sequences of MMTV in HBC have a similar oncogenic effect.